Perancangan Video Iklan Layanan Masyarakat Alat Kontrasepsi Berbasis Online Sebagai Sarana Informasi Program Keluarga Berencana - Cahyono, Eko; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Fungsian failure problems or lack of contraception is still quite common among people who use family planning program. At least the report noted the failure of contraception in the period 2010-2013 amounted to 3846 report (BKKBN). Responding to the issue of the National Family Planning Coordinating Board (BKKBN) gives advice to follow family planning method Long Term (LTM). LTM with contraceptive tool, the contraceptive IUD and implants, it has a higher success rate in controlling the birth rate. In addition to a higher level of security, long-term contraception tool also has a longer lifetime of 5-10 years as user preferences, so that the contraceptive is also considered more efficient in cost pemakiannya. But people still do not know clearly about contraceptives and more use of short-term contraceptives that birth control pills and injectables which also has a lower level of security. Of the existing problems the author aims to design video public service announcements online-based contraceptives as a means of family planning information program.Kata Kunci: Solutions, Problem, and Answer